2011
DOI: 10.1002/ijc.25962
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR‐335 is crucial for the BRCA1 regulatory cascade in breast cancer development

Abstract: The expression of microRNAs is altered in various cancer types, leading to their definition as onco-and tumor-suppressor microRNAs. In our study, we investigated the role of miR-335 in the formation of sporadic human breast cancer and its involvement in the regulatory network of the breast cancer susceptibility gene BRCA1. To validate single components of the BRCA1 cascade, microRNA overexpression was performed in a cell culture model with subsequent protein analysis and luciferase reporter assays. Here, we we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 34 publications
5
77
0
2
Order By: Relevance
“…Some microRNA is also suggested by initial studies to confer resistance to commonly used chemotherapy drugs such as Fulvestrant [15] . This complements studies suggesting that microRNAs can regulate BRCA1 cascades and thus DNA damage programs in cancer cells during cancer development [20] . For a brief review of breast cancer classification, screening tests, current treatment and expected outcomes (Table 1).…”
Section: Introductionsupporting
confidence: 78%
“…Some microRNA is also suggested by initial studies to confer resistance to commonly used chemotherapy drugs such as Fulvestrant [15] . This complements studies suggesting that microRNAs can regulate BRCA1 cascades and thus DNA damage programs in cancer cells during cancer development [20] . For a brief review of breast cancer classification, screening tests, current treatment and expected outcomes (Table 1).…”
Section: Introductionsupporting
confidence: 78%
“…Tavazoie et al (2008) reported that miR-335 can repress breast cancer migration and invasion through targeting SRY-related HMG-box 4 (SOX4) and tenascin C. By simultaneously regulating the known breast cancer 1 (BRCA1) activators, ER-α, IGF1 and Sp1, and the repressor ID4, miR-335 exerts its tumor-suppressive function by decreasing cell viability and inducing apoptosis (Heyn et al, 2011).…”
Section: Mir-335mentioning
confidence: 99%
“…In the male reproductive system, Id4 loss results in significantly reduced seminal vesicle size, prostatic intraepithelial neoplasia (PIN) lesions and sterility (Sharma et al, 2013), while a recent study in the mammary gland has shown that Id4 governs ductal elongation and branching via the Id4 target p38MAPK (Dong et al, 2011). In breast epithelial cells, Id4 negatively controls expression of the key tumor suppressor Brca1 (Beger et al, 2001) and also suppresses miR335, a positive regulator of Brca1 (Heyn et al, 2011). In the context of breast cancer, overexpression of Id4 tightly correlates with the 'triple-negative' subtype (de Candia et al, 2006;Wen et al, 2012) and inversely correlates with expression of BRCA1 and estrogen receptor α (ERα; Esr1) (Molyneux et al, 2010;Roldán et al, 2006).…”
Section: Introductionmentioning
confidence: 99%